Marketing cultural - guia de proposta para solicitação em diversas entidades - Machado, Marcos Vinicios Machado (2010)
In this study, the Cultural Marketing is directly associated to the term which expresses the patronage polices of public funding for culture, where it is assumed that both the coordination between state, private and the field of cultural producers as the goals of the funding. Tax incentives are part of the financing system and constitute an instrument of government to direct and encourage the presence of private resources and strategic segments. This work is basically composed of two distinct parts. In the first part delimit the conceptual field, passing by a brief historical background, trying to identify from empirical trends Patronage in Brazil, and by drawing the guidelines of the cultural policies during the period of democratization in Brazil. The second part presents some of the main sponsors of the culture in Brazil, values and forms of investment, covering the period from 2008 and the presentation of the major steps required in developing a Cultural Project.